A star is born (1954) [videorecording (DVD)] - Cukor, George, 1899-1983; Garland, Judy; Mason, James, 1909-1984; Carson, Jack, 1910-1963 (Warner Home Video, 2010)
A movie star declining in popularity marries a shy young actress whose fame grows to eclipse his.